Study of autonomic sympatho-vagal modulation in different trimesters of pregnancy - Sonia Kochhar; Jit Swaran; Ashwani Ummat (International Journal of Medical Research and Review, 2016)
Introduction: Various physiological conditions are known to influence functional activity of ANS and one such state is pregnancy. Pregnancy is associated with profound but temporary and reversible hemo-dynamic changes in mother to support fetal development and growth but without permanent deleterious effects in the mother.Material & Methods: Functional status of Autonomic Nervous System during 1st, 2nd and 3rd trimester of pregnancy was studied in 75 pregnant women in all three trimesters of pregnancy (25 each) and results were compared among them and with another 25 non-pregnant women taken as control. Parasympathetic activity was assessed by Standing to Lying down ratio, 30:15 ratio, Valsalva ratio and Tachycardia ratio. The assessment of sympathetic activity was done by tests viz. CPT, HGT and GSR.Results: Parasympathetic activity was significantly reduced in 3rd trimester of pregnancy in comparison to non-pregnant controls as well as 1st and 2nd trimesters. The sympathetic activity showed significant rise in sympathetic nervous system activity during 3rd trimester of pregnancy in comparison with the changes in non-pregnant controls as well as 1st & 2nd trimester of pregnancy.Conclusion: Although ANS play a central role in the adaptation of hemodynamic to various demands of pregnancy yet its failure to achieve the required goal during different trimesters of pregnancy is poorly understood and needs to be investigated. This havoc of sympatho-vagal modulation in pregnancy can be attributed to orthostatic dys-regulation occurring due to deficiency of autonomic nervous control mechanisms in pregnancy and we have tried to prove this in our study.